Strategi Pengelolaan SDM Dalam Menyikapi Kebijakan Efisiensi Pemerintah Pada Swiss-Belhotel Rainforest Kuta – Bali - I Made Adhika Dwi Kusuma; Muhammad Nasir Hamzah; Megawaty (Movere Journal, 2026)
Government efficiency policies have significantly affected the hospitality industry, particularly hotels that rely on government-related market segments such as Meetings, Incentives, Conventions, and Exhibitions (MICE), thereby requiring adaptive and strategic human resource management (HRM). However, empirical studies that specifically examine how HRM strategies are practically implemented in response to government efficiency policies remain limited, especially within the context of the hospitality industry in Bali. This study aims to analyze the human resource management strategies implemented by Swiss-Belhotel Rainforest Kuta – Bali in responding to government efficiency policies and to examine adaptive HRM practices in sustaining organizational performance under external pressures. This research employs a qualitative descriptive approach using a case study method. Data were collected through in-depth interviews with management and employees, direct observation of hotel operational activities, and analysis of supporting documents. Data analysis was conducted using NVivo 14 to identify themes, patterns, and adaptive HRM strategies. The findings reveal that government efficiency policies resulted in a decline in demand from government market segments, particularly MICE activities. In response, management implemented HRM strategies based on Strategic Human Resource Management (SHRM) and the Resource-Based View (RBV), including multiskilling training, flexible work scheduling, cross-departmental collaboration, and workload optimization. These strategies were supported by transparent internal communication and supportive leadership, enabling the hotel to maintain organizational performance and operational sustainability amid external pressures.